Politics in Russia a reader - Ostrow, Joel M. (SAGE Publications CQ Press, 2013)
A comprehensive reader composed of landmark selections, guided by the insight that to understand contemporary Russia, students need to know that there are strongly competing interpretations of Russian politics past and present .